2014
DOI: 10.1038/nature13836
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cooling by strong magnetic fields in white dwarf stars

Abstract: Isolated cool white dwarf stars more often have strong magnetic fields than young, hotter white dwarfs, which has been a puzzle because magnetic fields are expected to decay with time but a cool surface suggests that the star is old. In addition, some white dwarfs with strong fields vary in brightness as they rotate, which has been variously attributed to surface brightness inhomogeneities similar to sunspots, chemical inhomogeneities and other magneto-optical effects. Here we describe optical observations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 32 publications
2
47
3
Order By: Relevance
“…The convective coupling occurs at T eff values lower than 6000 K in white dwarfs, hence the suppression of convection is not expected to impact cooling rates for warmer remnants. This argument contradicts the suggestion from Valyavin et al (2014;see their Figure 3(a)) that the suppression of convection changes the cooling rates and explains the observed temperature distribution of magnetic white dwarfs, for which their coolest bin is at T eff = 6000 K. To demonstrate it quantitatively, this section presents new evolution sequences that we have computed with our state-of-the-art white dwarf evolutionary code (Fontaine et al 2001;Fontaine et al 2013). To fully appreciate the results, we also review the important properties of white dwarf cooling in Section 2.3.…”
Section: Evolutionary Modelscontrasting
confidence: 54%
See 3 more Smart Citations
“…The convective coupling occurs at T eff values lower than 6000 K in white dwarfs, hence the suppression of convection is not expected to impact cooling rates for warmer remnants. This argument contradicts the suggestion from Valyavin et al (2014;see their Figure 3(a)) that the suppression of convection changes the cooling rates and explains the observed temperature distribution of magnetic white dwarfs, for which their coolest bin is at T eff = 6000 K. To demonstrate it quantitatively, this section presents new evolution sequences that we have computed with our state-of-the-art white dwarf evolutionary code (Fontaine et al 2001;Fontaine et al 2013). To fully appreciate the results, we also review the important properties of white dwarf cooling in Section 2.3.…”
Section: Evolutionary Modelscontrasting
confidence: 54%
“…It is therefore essential, at this stage, to build precise model atmospheres and evolution sequences for these peculiar degenerate stars. It has been suggested for a long time that convection is completely inhibited in HFMWDs (Wickramasinghe & Martin 1986;Valyavin et al 2014), although this has not yet been verified with realistic simulations. Furthermore, Kepler et al (2013) suggest that small undetected magnetic fields could impact the mass distribution of cool convective white dwarfs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Valyavin et al (2014) showed that convection is completely suppressed starting from surface magnetic fields of the order of 10 MG, and therefore strong magnetic fields slow down the white dwarf cooling process. As a consequence, the CHZ for strongly magnetic white dwarfs may extend even more in time, well beyond 8 Gyr.…”
Section: Introductionmentioning
confidence: 99%